Professional Development Through Optimizing of School Principal Role in Handling Human Resources Management - Yogyantoro Yogyantoro; Noer Doddy Irmawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
School principals in today's school community hold collaboration between educator, school staff, distribute accessible resources, improve educator professional development, and perform students across their academic and curriculum on standardized tests. The principal's duties are inclusive, as all aspects of school management are directly or indirectly are his/her responsibility. In general, the principal has the responsibilities to manage (1) detailed organization of the school. (2) curriculum development. (3) assigning duties to staff and supervising them, and (4) general operation of school facilities. The success of school education is largely determined by the success of the principal in managing the educators and staff available at the school. In this case, increased productivity and work efficiency can be achieved by improving the behavior of school teachers and educational staff by applying different human resource management concepts and techniques. In human resource management, school principals are the key to success in achieving quality education. School leaders must constantly strive to develop human resources both educators and educational staff in order to produce good quality of education.